Droplet microfluidics: from proof-of-concept to real-world utility?. Issue 67 (23rd July 2019) - Suea-Ngam, Akkapol; Howes, Philip D.; Srisa-Art, Monpichar; deMello, Andrew J.
Abstract : Droplet microfluidics constitutes a diverse and practical tool set that enables chemical and biological experiments to be performed at high speed and with enhanced efficiency when compared to conventional instrumentation. Abstract : Droplet microfluidics constitutes a diverse and practical tool set that enables chemical and biological experiments to be performed at high speed and with enhanced efficiency when compared to conventional instrumentation. Indeed, in recent years, droplet-based microfluidic tools have been used to excellent effect in a range of applications, including materials synthesis, single cell analysis, RNA sequencing, small molecule screening, in vitro diagnostics and tissue engineering. Our 2011 Chemical Communications Highlight Article [ Chem. Commun., 2011, 47, 1936–1942] reviewed some of the most important technological developments and applications of droplet microfluidics, and identified key challenges that needed to be addressed in the short term. In the current contribution, we consider the intervening eight years, and assess the contributions that droplet-based microfluidics has made to experimental science in its broadest sense.